Responses of Megacyllene andesiana and Oreodera bituberculata (Coleoptera: Cerambycidae) to anti-2,3-hexanediol, fuscumol, and fuscumol acetate in Peru - Aguirre Gil, Oniel Jeremías; Paredes Espinosa, Richard; Egoávil Jump, Giannfranco; Allison, Jeremy Dean (Cambridge University Press, 2024)
Management of phytosanitary and biosecurity risks associated with the Cerambycidae focuses on prevention and early detection. Semiochemical-baited traps are an important component of these management efforts. Cerambycid pheromones are often screened in field trials to develop inventories of which species can be surveyed with which semiochemicals. We report field trials of two types of intercept traps (four- and three-sided panel traps) baited with known Cerambycidae pheromones aimed to capture Peruvian fauna. Intercept traps were baited with anti-2,3-hexanediol, fuscumol, and fuscumol acetate alone and in binary and ternary blends. The most frequently captured species was Megacyllene andesiana (Casey) (Coleoptera: Cerambycidae) (n = 268), followed by Oreodera bituberculata Bates (Coleoptera: Cerambycidae) (n = 59), Discopus eques Bates (Coleoptera: Cerambycidae) (n = 37), and Aegomorphus longitarsis (Bates) (Coleoptera: Cerambycidae) (n = 31). Trap type did not affect capture rates. Male and female M. andesiana were attracted by anti-2,3-hexanediol. The addition of fuscumol, fuscumol acetate, or the combination of fuscumol and fuscumol acetate reduced male M. andesiana captures, whereas the addition of fuscumol and the combination of fuscumol and fuscumol acetate reduced the response of female M. andesiana. Male O. bituberculata were attracted to traps baited with fuscumol, and this response was reduced by the addition of fuscumol acetate, whether or not anti-2,3-hexanediol was present.